The Role of Appearance Self-schema in the Perceived Impact of Fitspiration Images on the Self and Others: A Study on Body Image - Ahadzadeh, Asharf Sadat; Amini, Mansour; Wu, Shin Ling; Haolin, Zhou (Makara Human Behavior Studies in Asia, 2022)
Exposure to Instagram Fitspiration images creates negative perceptions toward one’s body. Drawing on third-person effect (TPE) theory, this study aims to explain such feelings among viewers and examine the effect of appearance self-schema as an underlying cause of negative body image and the perceived impact of Fitspiration images on the self and others. A total of 301 university students who were viewers of Fitspiration images were recruited to complete a survey on demographic characteristics, body image, appearance self-schema, and the perceived impact of Fitspiration images on the self and others. Results show that the perceived effect of Fitspiration is greater on others than on the self. Appearance self-schema and the perceived impact of the media on others are negatively correlated with body image. Moreover, appearance self-schema positively counts for the perceived impact of Fitspiration images on the self and others. The robustness of TPE theory was confirmed in the context of Fitspiration images. Theoretically, TPE theory was expanded by introducing appearance self-schema as a predictor of first- and third-person perceptions. Some practical recommendations were made for young viewers and educationalists about the physical and mental health education related to the findings of this study.